What is the utility function of the Brazilian investor? - Tessari, Juliana (2017)
We analyze which utility function would best represent the Brazilian representative investor with a one-month investment horizon who has to allocate his wealth across three main asset classes (bonds, equities, and risk free). To do this, we compute the optimal portfolio weights by considering four different specifications for the utility function: (i) mean-variance, (ii) constant relative risk aversion (expected utility functions), (iii) ambiguity aversion, and (iv) loss aversion (non-expected utility functions). We compare the optimal portfolio weights to the empirical portfolio - computed by considering the market value of all the assets in our sample - using the Mahalanobis distance. Our results indicate that the traditional utility function, the mean-variance utility, should not be used to represent the behavior of the Brazilian investor. All other utilities are statistically equal and could be used to compute optimal portfolios for the Brazilian investor. However, the constant relative risk aversion (CRRA) and the ambiguity aversion functions are only justified for extremely high levels of risk aversion. As the loss averse function showed the lowest Mahalanobis distance, we propose that the Brazilian investor is best represented by a utility function that incorporates aversion to losses, in which the decrease of utility caused by a loss is much greater than the increase caused by a gain of equal magnitude. Moreover, this different impact of gains and losses on the investor\'s utility leads individuals to behave as investors with high risk aversion and justifies the fact that loss-aversion preferences have also been widely used to explain why the high risk premium might be consistent with high levels of risk aversion.